2020
DOI: 10.1177/1096348020927453
|View full text |Cite
|
Sign up to set email alerts
|

Improving Tourism Innovation Performance: Linking Perspectives of Asset Specificity, Intellectual Capital, and Absorptive Capacity

Abstract: This study seeks to better understand the link of a tourism firm’s intellectual capital to innovation performance, empirically testing the mediating role of absorptive capacity and moderating effect of asset specificity. Findings from 217 Chinese tourism firms indicate that absorptive capacity plays a mediating role in the capital–performance link, and the effect of social capital to absorptive capacity is highest when asset specificity is at an intermediate level, having an inverted “U” shape. The result indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…Lee et al, 2019). This capacity is particularly vital in hospitality and tourism, as enterprises’ innovation activities depend heavily on obtaining exploitative knowledge along with filtering, incorporating, or amalgamating current intellectual knowledge (Wu, 2020). Another important capacity relevant to innovation is collaborative ability.…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al, 2019). This capacity is particularly vital in hospitality and tourism, as enterprises’ innovation activities depend heavily on obtaining exploitative knowledge along with filtering, incorporating, or amalgamating current intellectual knowledge (Wu, 2020). Another important capacity relevant to innovation is collaborative ability.…”
Section: Resultsmentioning
confidence: 99%
“…Other research has shown that firm size (e.g. number of employees or rooms, as in hotels) is positively related to only the realized aspect of absorptive capacity (Thomas and Wood, 2014;Wu, 2020) or to the unidimensional measure of absorptive capacity (C orcoles Muñoz et al, 2022) in hospitality contexts. Organizations' adoption practices have also been found to positively correlate to the number of employees (Lenox and King, 2004).…”
Section: Ijchm 3510mentioning
confidence: 99%
“…Second, inconsistent findings regarding the intellectual capital-absorptive capacity association (Engelman et al. , 2017; Wu, 2020) suggest the existence of a viable moderator. For example, Ahmed et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They suggested activation triggers like crisis, radical innovations and policy changes that promote responses to new ideas. Second, inconsistent findings regarding the intellectual capitalabsorptive capacity association (Engelman et al, 2017;Wu, 2020) suggest the existence of a viable moderator. For example, Ahmed et al (2020) found that absorptive capacity does not intervene in the relationship between intellectual capital and performance and that social capital was a weak predictor of performance, while human capital and organizational capital had a profound positive impact.…”
Section: Environmental Turbulence As Potential Moderatormentioning
confidence: 99%